Formulation, Characterization, and In Vitro Evaluation of Sunscreen Cream Containing Kenikir (Cosmos caudatus Kunth.) Extract and Chicken Bone Collagen Hydrolysate - Zukhruf, Annisa; Afifah, Ika Qurrotul (Universitas Airlangga, 2025)
Background: Sunlight is a major contributor to skin damage, including erythema, pigmentation, premature aging, and other related conditions. Kenikir extract contains flavonoid derivatives, which have the potential to act as sunscreen due to the presence of chromophore groups that can reduce the intensity of sun exposure on the skin. In this study, sunscreen was made from kenikir extract with the addition of collagen hydrolysate. Objective: This study aims to assess the effectiveness and characteristics of various sunscreen cream formulations produced. Methods: Kenikir extract was obtained through ethanol-based maceration, while collagen hydrolysate was prepared by isolating chicken bone collagen using acetic acid solvent, followed by enzymatic hydrolysis with bromelain. Four sunscreen cream formulations were developed using various concentrations of kenikir extract and collagen hydrolysate. The creams were characterized by evaluating sun protection factor (SPF), percent erythema, percent pigmentation, organoleptic properties, acceptance testing, homogeneity, pH, viscosity, centrifugation, and spreadability. Results: The cream containing kenikir extract was effective as sunscreen with an SPF of 45.59, erythema of 1.96%, and pigmentation of 1.27%. It also exhibited homogeneity, with a pH of 7.83 and a viscosity of 46,700 cps, which met the permissible range for sunscreen use. The stability test indicated that it was stable, with no separation observed. Conclusion: Sunscreen cream containing kenikir extract has the potential to protect the skin from excessive sun exposure due to the effectiveness and good characteristics according to the Indonesian National Standard (SNI).